The Effect of Simultaneous Contralateral White Noise Masking on Cortical Auditory Evoked Potentials Elicited by Speech Stimuli - Felix, Luiza Dandara de Araújo; Menezes, Pedro Lemos; Oliveira, Lisiane Vital de; Batista, Carlos Henrique Alves; Carnaúba, Aline Tenório Lins; Andrade, Kelly Cristina Lira de (International Archives of Otorhinolaryngology, 2024)
Introduction Noise obscures speech signal, causing auditory masking. The effects of this masking can be observed through the cortical auditory evoked potentials (CAEPs). White noise, in turn, has an effect on the auditory cortex, interfering, for example, with lexical decision making.Objective To analyze the effect of simultaneous masking by contralateral white noise on CAEPs elicited by speech stimuli.Methods Cross-sectional observational analytical study carried out with 15 participants of both sexes, who were submitted to CAEPs in two conditions: 1) without noise; 2) with white noise at 100 dBSPL intensity, contralaterally and simultaneously. To compare these conditions, the Student t test or the Wilcoxon test were used, depending on the sample normality. Differences with p values < 0.05 were considered significant.Results: When white noise was presented contralaterally and simultaneously to the CAEPs with speech stimulus, an increase in P1, N1 and P2 wave latencies was observed. P1 and P2 amplitudes and N1-P2 peak to peak amplitude also increased, unlike N1 amplitude, which decreased. The differences were significant for P1 and P2 wave latencies and for P2 wave amplitude.Conclusion The simultaneous masking effect was observed from the morphological alterations of the CAEPs with speech stimulus when white noise was presented in the contralateral ear. There was a significant increase in P1 and P2 wave latencies, as well as in P2 wave amplitude.
Keywords: electrophysiology; auditory evoked potentials; noise